Strategic Integration of Green Innovation, Green Behavior, and Information Systems for Sustainable Business Performance & Competitiveness - Abubakar, Ahmed; Khalifa, Mohammed Mahmuda; Elbasset, Fatma Hassan Abd; Alkharusi, Buthaina (International Journal of Management and Sustainability, 2022)
Due to the emergence of the need for sustainable development, the COVID-19 pandemic, and the need to conduct business within the framework of the Fourth Industrial Revolution, businesses are facing a difficult environment in which they struggle to achieve and maintain competitiveness. To conduct business in today's globalized environment, innovation, behavior, and information are becoming increasingly important constructs to consider. This article investigates the effects of green innovation, green behavior, and information systems on the sustainable performance and competitiveness of businesses. The relationships between the constructs are discussed in terms of long-term development and post-pandemic business trends. Structural equation modeling is used to analyze data collected from 221 managers of small and medium-sized enterprises. All hypotheses are supported, and the results reveal the influence of green innovation, green behavior, and information systems on sustainable business performance and competitiveness. The findings are discussed, and managerial implications are highlighted, along with suggestions for future research.